(untitled) (Zaporizhzhia Historical Review, 2017)
The way sand methods of establishment and implementation of new Soviet educational system at the seized territories of Ternopil region are presented in this article. We studied documents of the state and party archives of Ternopil region as a fundamental material for the research. The new system of education, which was supposed to follow the objectives and principles of the new soviet occupation regime, had to be effective in ideological and staff assistance for its social, economic and political institutions. We also analyzed various aspects of the Sovietization process of the region, where humanitarian aspect was of great importance that was mostly defined by the principles of official policy in cultural and educational life of the society. This expansion was comprehended as a means of communist ideology for imposing and development of a „new personality‟ that would meet requirements of the regime. After taking the control over almost all educational, scientific and cultural institutions, the state began to develop personal worldview in the necessary direction in Western Ukraine.